2019
DOI: 10.3390/v11060546
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Cytochrome b5 Is a Restriction Factor for Soybean Mosaic Virus

Abstract: Soybean mosaic virus (SMV) is one of the most destructive viral diseases in soybeans (Glycine max). In this study, an interaction between the SMV P3 protein and cytochrome b5 was detected by yeast two-hybrid assay, and bimolecular fluorescence complementation assay showed that the interaction took place at the cell periphery. Further, the interaction was confirmed by co-immunoprecipitation analysis. Quantitative real-time polymerase chain reaction analysis revealed that GmCYB5 gene was differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…After SMV infection, SMV virions would robustly replicate and accumulate in soybean susceptible cultivars, while a small amount of SMV could be detected in the inoculated leaves of soybean resistant cultivars at the early stage of infection. Although the resistant cultivar showed extreme resistance to viruses, a slower host response allows a certain degree of virus replication and movement before conferring virus arrest [53,54]. After SMV infection, the expression of GmRPS8 was induced at the early stage of infection in the resistant Kefeng No.1 plants, while significantly upregulated in the susceptible Nannong 1138-2 plants (Figure 1), indicating that the expression of GmRPS8 was related to SMV replication.…”
Section: Discussionmentioning
confidence: 99%
“…After SMV infection, SMV virions would robustly replicate and accumulate in soybean susceptible cultivars, while a small amount of SMV could be detected in the inoculated leaves of soybean resistant cultivars at the early stage of infection. Although the resistant cultivar showed extreme resistance to viruses, a slower host response allows a certain degree of virus replication and movement before conferring virus arrest [53,54]. After SMV infection, the expression of GmRPS8 was induced at the early stage of infection in the resistant Kefeng No.1 plants, while significantly upregulated in the susceptible Nannong 1138-2 plants (Figure 1), indicating that the expression of GmRPS8 was related to SMV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that a single dominant gene, designated as Rsc15, conferred the SMV resistance, and it was located between Sat_213 and Sat_286 with distances of 8.0 and 6.6 cM, respectively. The candidate gene Glyma.18g154900 in RN-9 encodes the cytochrome protein GmCYB5 targeting the P3 protein of SMV to inhibit its proliferation (Luan et al, 2019) [183]. This novel resistance gene has never been found in germplasm infected by American SMV strains.…”
Section: Other Smv Gene Definitionsmentioning
confidence: 99%
“…The Rsv4 locus can resist all the SMV strains at the seedling stage but often produces systemic symptoms in mature plants [ 14 ]. To date, several anti-SMV genes have been cloned, including GmPEX14 [ 15 ], GmAKT2 [ 16 ], GmPP2C3a [ 17 ], GmCnx1 [ 18 ], GmeEF1a [ 19 ], GmSN1 [ 20 ], GmKR3 [ 21 ], GmCYB5 [ 22 ], GmF3H1, GmF3H2 and GmFNSII-1 [ 23 ], GmST1 [ 24 ], Rsc4-3 [ 25 ], GmPAP2.1 [ 26 ] and GmCAL [ 27 ]. The functional mechanisms of these anti-SMV genes are mainly through regulating immune responses via increasing the contents of phytohormones (ABA or SA) or secondary metabolites (e.g., isoflavone) or R genes’ recognition of viral-encoded protein to interfere with the replication or movement of SMV in the soybean host cells.…”
Section: Introductionmentioning
confidence: 99%